Provisional Agenda for the Twenty-First Meeting of the International Monetary and Financial Committee. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The crisis brought the financial system to the verge of systemic collapse and raised the prospect of depression and deflation. Central banks helped defuse these threats, including through exceptional measures. Considerable efforts are now under way to draw policy lessons from the crisis. For central banks, the crisis seems to provide three important lessons for policy frameworks-mainly concerning systemic financial stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Agenda; IMF Chairman; PP; Twenty-First Meeting Of The International Monetary